USE OF ARCHITECTURAL PANELS PROVIDING AGROINDUSTRIAL WASTE IN THE CONTROL OF THE THERMAL ENVIRONMENT AND IN THE PRODUCTIVE PERFORMANCE OF LAYING CHICKENS - Duarte, S.G.; Bueno, L.G.F.; Sartori, D.L.; Rezende, J.P.A.; Souza, S.R.L.; Glavina, A.S.G.; Gotardi, P.A. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The growth in the poultry market demanded that new measures be taken, so that the climate would interfere less and less with the production of eggs, trying to reduce the thermal stress of the birds. In this study, the efficiency of the use of panels made of agroindustrial residues in egg production was verified. In this experiment, three plants were used, being number 1 Conventional: masonry and closure with metal screen, cover with fiber cement tile and use of plastic liner; 2 with masonry fence and closure with metal screen, cover with fiber cement tile and without lining; 3 fence in masonry and closure with metallic screen, cover with asbestos cement tiles and use of lining with the panels, that through the use of black globe and with the aid of dataloggers there was the records of ITGU and the collection of the production of during the three week period. We used the randomized design in Blocks and for the analysis was made Anova and the Tukey Test (5%). By means of these results, it was verified that the use of agroindustrial waste panels did not obtain a larger significant egg production in relation to aviaries without the use of this isolator and does not hear improvement in the range of ITUU calculated for the presence of the presence of the aviary of the panels.